Factors Affecting Subjective Symptoms in Children with Pes Planovalgus Deformity: A Study Using the Oxford Ankle Foot Questionnaire - Min, Jae Jung; Kwon, Soon Sun; Sung, Ki Hyuk; Lee, Kyoung Min; Chung, Chin Youb; Park, Moon Seok (Journal of Bone and Joint Surgery, 2020)
Background:Idiopathic pes planovalgus is one of the most common foot deformities in children and adolescents. However, there is a discrepancy between subjective symptoms and radiographic severity in idiopathic planovalgus deformity, and very few studies have investigated this aspect. Further, the assessment of subjective symptoms in patients with pes planovalgus requires a quantitative scoring system for making meaningful comparisons, such as the Oxford Ankle Foot Questionnaire for Children (OxAFQ-c) and that for parents (OxAFQ-p). Therefore, the purpose of this study was to evaluate the factors affecting the symptoms of idiopathic planovalgus using the OxAFQ.Methods:All patients who were ≤18 years of age, had visited our clinic for the evaluation of pes planovalgus deformity, and had completed the OxAFQ were included in this study. The anteroposterior talo-first metatarsal, lateral talo-first metatarsal, and hallux valgus angles were measured on weight-bearing radiographs. The data were analyzed using a multiple regression model, with age, sex, and radiographic indices as explanatory variables.Results:Overall, 123 patients were enrolled in this study, and 246 standing foot radiographs were evaluated along with scores in each domain of the OxAFQ. The factors affecting physical domain scores in the OxAFQ-c were female sex (p = 0.047) and the anteroposterior talo-first metatarsal angle (p = 0.033). Age of ≥10 years was a significant factor (p < 0.05) affecting all domains in both the OxAFQ-c and OxAFQ-p other than the physical domain score.Conclusions:Although pes planovalgus deformity is 3-dimensional, the forefoot abduction component of the deformity should be carefully assessed as it is closely related to subjective symptoms. Further, in female patients with a more severe anteroposterior talo-first metatarsal angle, an aggravation of symptoms with aging should be expected when managing pes planovalgus deformity.Level of Evidence:Prognostic Level IV. See Instructions for Authors for a complete description of levels of evidence.
Keywords: Adolescent; Child; Diagnostic Self Evaluation; Female; Flatfoot; Humans; Male; Radiography; Retrospective Studies; Self Report; Severity of Illness Index